2023
DOI: 10.1590/1519-6984.247374
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, distribution and relative abundance of the mosquito fauna (Diptera: Culicidae) of Malakand and Dir Lower, Pakistan

Abstract: The present study was conducted to evaluate the diversity, distribution (C) and relative abundance (RA) of the mosquito fauna (Diptera: Culicidae) of Malakand and Dir Lower, Pakistan. Collection of specimens (n = 1087) was made during September 2018 to July 2019 at six different habitats including freshwater bodies, rice fields, animal sheds, indoors, drains and sewage waters. Specimens were collected through light traps, pyrethrum spray, aspirators and nets and subsequently killed, preserved and then arranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Mosquitoes are important disease vectors, and their diversity and distribution determine the course of disease transmission and the ecological status of the native environment. As discussed above, the taxonomic identification revealed the presence of four species belonging to three genera: The studies were conducted by Ali and Rasheed [28]; Attaullah et al [29]; Manzoor et al [11]; and Khan et al [30]. As for Aedes albopictus, previous studies such as [31] has shown its presence in Peshawar, though in other regions of the city as compared to the ones studied in the current study.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Mosquitoes are important disease vectors, and their diversity and distribution determine the course of disease transmission and the ecological status of the native environment. As discussed above, the taxonomic identification revealed the presence of four species belonging to three genera: The studies were conducted by Ali and Rasheed [28]; Attaullah et al [29]; Manzoor et al [11]; and Khan et al [30]. As for Aedes albopictus, previous studies such as [31] has shown its presence in Peshawar, though in other regions of the city as compared to the ones studied in the current study.…”
Section: Discussionsupporting
confidence: 49%
“…Table 2), Aedes aegypti was found to be a frequent specie in the study sites considered in this research. Existing published literature show that the specie is widely distributed in Peshawar, Charsadda, Lahore, and Swat (clumped distribution mainly spread by travel and heterogeneous environment), while infrequently distributed in Dir Lower and Malakand owing to the fact that the latter districts have different climatic and ecological conditions [29][30][31][32]. Lastly, Armigeres subalbatus' presence was only restricted to district Charsadda as shown above (vid.…”
Section: Discussionmentioning
confidence: 85%
“…-2). [1] recorded 14 species from Malakand and Dir Lower; of which 9 species were Dominant, 4 species were Sub-dominant and 1 species was Satellite species. Relative Abundance of all these species is displayed in a line graph (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They are the primary carriers of many parasitic and viral illnesses that affect humans and other domestic animals. Many diseases and illnesses, like dengue, malaria, arboviruses, filariasis, and western equine viruses, are transmitted by different species of mosquitoes [1] . With the use of pictorial identification keys larvae and adult mosquitoes may be classified and grouped according to their morphological features, adult male and female species can be distinguished by looking at their mouth parts like antennae, palps and wings.…”
Section: Introductionmentioning
confidence: 99%
“…The Aedes mosquitoes (Aedes aegypti or Aedes albopictus) transmit dengue fever and other vector-borne infections 1,2 . The number of mosquitoes in an area influences the intensity of a dengue epidemic, and the mosquito population is influenced by several environmental variables [4][5][6] , such as the movement of humans, their location, and climatic conditions [7][8][9] . The number of people, houses, and mosquitoes has increased due to urbanization.…”
Section: Introductionmentioning
confidence: 99%